The Therapeutic and the Transgressive: Chinese Fansub Straddling between Hollywood IP Laws and Chinese State Censorship - Ying Zhu (Global Storytelling)
Fansub has played a significant role in recent years in introducing otherwise unavailable foreign AV content to China via file transfer on pirate websites that bypass or play cat-and-mouse games with both regulators and copyright holders. Fansub further provides opportunities for participants to preserve the integrity of the source content that challenges mainstream conventions and values. This article provides an overview of fansubbing in China and discusses the complex issues involving international IP law, China’s selective compliance with such laws, and the Chinese government’s censorship of media and entertainment content. Specifically, the article traces the evolution of Chinese piracy of Hollywood film and television from counterfeit to fansub to tease out the larger issues of access, advocacy, and copyright infringement. Neither the legal nor the political hazard has deterred die-hard fansubbers from their “transgressions.” In discussing fansub motivations, the article further examines both the transgressive and affirmative experiences of Chinese fansub through the lens of the therapeutic effects.